2001
DOI: 10.1037/0735-7028.32.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and depression among college students: A decade later.

Abstract: Are suicidal thoughts and depression increasing or decreasing among college students? What life circumstances are the most critical to explore with depressed or suicidal college students? This article focuses on the rate of self-assessed depression and suicide among college students and examines contributing factors and help-seeking behavior. Results of our study indicated that 53% of the sample stated that they experienced depression since beginning college, with 9% reporting that they had considered committi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
216
1
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(254 citation statements)
references
References 12 publications
23
216
1
14
Order By: Relevance
“…Within the depressed group 17.4% (n = 17) reported suicidal intent and 58.7% (n = 54) reported suicidal ideation, both of which were significantly related to depression severity for the sample in total and further were significant as risk factors associated with depression in the depressed group. The results support the literature as to the importance of such factors for depression, particularly for university students (Furr, Westefeld, McConnell, & Jenkins, 2001). Downloaded by [Derek Richards] at 01:24 10 January 2014…”
Section: Suicidesupporting
confidence: 80%
“…Within the depressed group 17.4% (n = 17) reported suicidal intent and 58.7% (n = 54) reported suicidal ideation, both of which were significantly related to depression severity for the sample in total and further were significant as risk factors associated with depression in the depressed group. The results support the literature as to the importance of such factors for depression, particularly for university students (Furr, Westefeld, McConnell, & Jenkins, 2001). Downloaded by [Derek Richards] at 01:24 10 January 2014…”
Section: Suicidesupporting
confidence: 80%
“…The results showed that 55.7% of the students had mild to severe depression. The results corresponds with previous international studies, Furr, Westefeld, McConnell, and Jenkins (2001) reported that 53% of the university students had depressive symptoms, and 40% of college students identified depression as their major concern (Woolfson,1997). Nationally, Almost 75% of the university students exhibited some degree of depressive symptoms (Hamdan-Mansour, Halabi, Dawani, 2008).…”
Section: Discussionsupporting
confidence: 76%
“…Given the potential negative consequences associated with poor test performance or failure, it is not surprising that students consistently cite exam and grade-related worries as their greatest sources of anxiety (Furr, Westefeld, McConnell, & Jenkins, 2001). The experience of high levels of exam-related anxiety is referred to in the literature as test anxiety (TA) and is characterized by cognitive, behavioural, and physiological responses induced by academic testing (Zeidner, 1998).…”
Section: Cover Page Footnotementioning
confidence: 99%